2023
DOI: 10.2174/1573413718666220513094848
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly Synthesis of Zinc Oxide Nanoparticles and Assessment of their Activities as Efficient Antioxidant Agents

Abstract: Background: The biosynthesis of zinc oxide nanoparticles (ZnO NPs) has received increasing attention in the field of nanotechnology due to their biomedical applications. With this aim, the present study was performed to synthesize biocompatible ZnO NPs using stems, leaves, and inflorescences extracts of the Tephrosia purpurea (T. purpurea) and Heliotropium indicum (H. indicum) medicinal plants. Objective: Synthesize ZnO NPs from T. purpurea and H. indicum and determine their ability as an alternative for tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The absence of a center of symmetry in wurtzite, combined with a remarkable electromechanical coupling, results in strong piezoelectric and pyroelectric properties, which makes using ZnO favorable in mechanical actuators and piezoelectric sensors [5,6]. Previous studies have confirmed that green synthesized ZnO NPs have significant photocatalytic, anticancer, antioxidant, and antibacterial activities, which has made them widely used in manufacturing several drugs and of great interest to researchers [7,8]. The plant Portulaca oleracea L. (purslane) grows sufficiently across various regions of the world, including Algeria.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a center of symmetry in wurtzite, combined with a remarkable electromechanical coupling, results in strong piezoelectric and pyroelectric properties, which makes using ZnO favorable in mechanical actuators and piezoelectric sensors [5,6]. Previous studies have confirmed that green synthesized ZnO NPs have significant photocatalytic, anticancer, antioxidant, and antibacterial activities, which has made them widely used in manufacturing several drugs and of great interest to researchers [7,8]. The plant Portulaca oleracea L. (purslane) grows sufficiently across various regions of the world, including Algeria.…”
Section: Introductionmentioning
confidence: 99%